Modeling the effects of concentration of solid nanoparticles in liquid feedstock injection on high-velocity suspension flame spray process - Mahrukh, Mahrukh; Kumar, Arvind; Gu, Sai; Kamnis, S.; Gozali, E. (American Chemical Society, 2016)
This paper presents the eﬀects of the concentration of solid nanoparticles in the liquid feedstock injection on the high-velocity suspension ﬂame spray (HVSFS) process. Four diﬀerent concentrations of solid nanoparticles in suspension droplets with various droplet diameters are used to study gas dynamics, vaporization rate, and secondary breakup. Two types of injections, viz. surface and group, are used. The group-type injection increases the eﬃciency of droplet disintegration and the evaporation process and reduces the gas cooling. The initiation of the fragmentation process is diﬃcult for small droplets carrying a high concentration of nanoparticles. Also, smaller droplets undergo rapid vaporization, leaving clogs of nanoparticles in the middle of the barrel. For larger droplets, severe fragmentation occurs inside the combustion chamber. For a higher concentration of nanoparticles, droplets exit the gun without complete evaporation. The results suggest that, in coating applications involving a higher concentration of nanoparticles, smaller droplet sizes are preferred.